Augmented Reality Using Brute Force Algorithm for Introduction to Prayer Movement Based - Furqan, Mhd; Ikhsan, Muhammad; Nasution, Irma Yunita (Scientific Journal of Informatics, 2021)
Proposed: Prayer is compulsory to worship for Muslims around the world. Prayer is a mandatory commandment from Allah SWT. However, the companions and the Madzhab of Islam have a different opinion but remain Saheeh as long as it does not stray away from the teachings of the Prophet and Al-Quran. This prayer movement consists of the prayer movement of the Madzhab, Imam Shafi'i, Imam Hanafi, Imam Hambali, and Imam Maliki. The Marker used 9 pieces with pictures of each movement. One marker has several shapes of the movements that are several object targets are listed in it. Methods: The Brute Force algorithm used is to match the String value. The Brute Force algorithm can recognize well any String value that is matched to the marker and data from the database. This algorithm is applied to Augmented Reality technology. This app is built using Augmented Reality technology that combines real-world and virtual worlds. Results: This technology is well recognized applied from the Brute Force algorithm, which can validate the match result String value between the database and marker. Novelty: This technology uses the camera to find suitable markers in order to display 3D objects if the marker and the database match. So that this built system can facilitate many circles in learning the prayer movements based on the prayer movement version of islamic high priest.